THE ROLE OF THIRD PARTIES IN THE REPAYMENT OF TAX DEBTS: AN ALTERNATIVE SOLUTION FOR STRUGGLING TAXPAYERS: THE ROLE OF THIRD PARTIES IN THE REPAYMENT OF TAX DEBTS: AN ALTERNATIVE SOLUTION FOR STRUGGLING TAXPAYERS - Lawe, Dedi Marsudi; Prasetyo, Dedy Ardian; Akkapin, Supaphorn (PENA LAW: International Journal of Law, 2025)
This research discusses the alternative of tax debt repayment by third parties as a solution for taxpayers in Indonesia who experience economic limitations in fulfilling their tax obligations. Amidst the low tax to Gross Domestic Product (GDP) ratio and tax compliance challenges in Indonesia, third-party involvement emerges as an innovative option that can help improve tax compliance and state revenue stability. This research uses normative legal methods with statutory, conceptual, and case approaches, and is analyzed through the lens of welfare state theory, utilitarianism theory, and development law theory. The results show that the involvement of third parties in tax repayment, if based on a valid civil law relationship, can be accommodated in the Indonesian tax system to reduce the burden on taxpayers who are financially incapable. Policy recommendations include the establishment of clear regulations, a strict monitoring system, as well as an updated tax information system to support third-party involvement. The contribution of this research is to provide a legal basis and policy recommendations to create a tax system that is more inclusive, adaptive, and supports the welfare of the wider community.